Analysis of Conscious and Unconscious Animation Audience Behavior in Children Using Neuromarketing - mohamad mahdi Izadkhah; sobhan yahyaie (مطالعات رسانه‌های نوین, 2017)
Neuromarketing is a new field of study focusing on consumer behavior based on unconscious responses. The newly-developed science makes use of a variety of techniques, one of which is Event-Related Potential which has been employed in the present study. The research seeks to identify the components of an animated character’s charm, based on the analysis of consumer behavior. The answers to questions about the design and production of the first animated character role are addressed and replied in this article. The present study, therefore, compares the traditional method (the question of the individual) with modern methods such as the event-related potential. The research then offers a fresh understanding of the way children respond regarding their tendency toward characters in programs meant for them. Some of the contradictions between what the children say and what’s going on in their subconscious were revealed by the study. Those results can be of valuable use for media policy-making and audience analysis.